2015
DOI: 10.1016/j.pisc.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The accidental assignment of function in the tautomerase superfamily

Abstract: Cg10062 from Corynebacterium glutamicum is a tautomerase superfamily member with the characteristic β Àα À β fold and catalytic Pro-1. It is a cis-3-chloroacrylic acid dehalogenase (cis-CaaD) homologue with high sequence similarity (53%) that includes the six critical active site residues (Pro-1, His-28, Arg-70, Arg-73, Tyr-103, and Glu-114). However, Cg10062 is a poor cis-CaaD: it has much lower catalytic efficiency and lacks isomer specificity. Two acetylene compounds (propiolate and 2-butynoate) and an alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…11,21 Compound 10 is not processed to any appreciable extent. 28 For both of the substrates, the hydration product (4 or 11, respectively) is not decarboxylated by the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…11,21 Compound 10 is not processed to any appreciable extent. 28 For both of the substrates, the hydration product (4 or 11, respectively) is not decarboxylated by the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…In the reversible docking models, the position of the electrophilic methylene bridge relative to Pro1A hints at the possibility of a covalent mechanism. Such catalytic proline residues reportedly possess the ability to mediate enzymatic conversions through covalent catalysis 66 . NAPQI has been shown to bind covalently to Pro1, while exhibiting non-covalent inhibitory activity 67 .…”
Section: Resultsmentioning
confidence: 99%
“…We directed our focus onto Cg10062 due to its catalytic superiority with ACA relative to cis- CaaD . Additionally, active site mutants of Cg10062 that lacked hydratase/decarboxylase activity were previously identified by Whitman .…”
Section: Resultsmentioning
confidence: 99%
“…We directed our focus onto Cg10062 due to its catalytic superiority with ACA relative to cis-CaaD. 43 Additionally, active site mutants of Cg10062 that lacked hydratase/ decarboxylase activity were previously identified by Whitman. 44 Incubation of variants E114Q and E114D with ACA, followed by analysis of the resulting products using 1 H NMR indicated that these variants possessed hydratase activity without hydratase/decarboxylase activity.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation